ChemInform Abstract: Rhodium Catalyzed Oxidative Coupling of Salicylaldehydes with Diazabicyclic Olefins: A One‐Pot Strategy Involving Aldehyde C—H Cleavage and π‐Allyl Chemistry Towards the Synthesis of Fused Ring Chromanones. Issue 52 (24th December 2013) - Jijy, E.; Prakash, Praveen; Shimi, M.; Pihko, Petri M.; Joseph, Nayana; Radhakrishnan, K. V.
Abstract The title reaction involves the first example of ring opening and ring closing of bicyclic hydrazines (I) via metal catalyzed oxidative coupling reaction.